Gastric antiulcer activity of Syngonanthus arthrotrichus SILVEIRA - Batista, L. M.; de Almeida, ABA; Magri, L. D.; Toma, W.; Calvo, T. R.; Vilegas, Wagner [UNESP]; Brito, ARMS (Pharmaceutical Soc Japan, 2004)
Syngonanthus arthrotrichus SILVEIRA, popularly known as sempre-vivas mini-saia, is found in mountains of the Espinhaco range in the Brazilian states of Bahia and Minas Gerais. Extracts of this species contain several constituents, including flavonoids which may have antiulcerogenic activity. An ethanolic extract (EEOH), and flavonoid-rich (FRF) and flavonoid-deficient (FDF) fractions obtained from the scapes of S. arthrotrichus were investigated for their ability to prevent ulceration of the gastric mucosa in mice and rats. In the ethanol/HCl-induced ulcer model, lansoprazole (30 mg/kg), EEOH (50, 100, 250 mg/kg) given orally protected the gastric mucosal against injury in mice by 79%, 78%, 73%, and 64% respectively. In the ethanol-induced gastric ulcer model in rats, the lansoprazole (30 mg/kg), FRF and FDF (100 mg/kg) significantly protected the gastric mucosal of rats by 65%, 38% and 25% respectively when compared with the negative control group. In indomethacin/ bethanechol-induced gastric ulcers, cimetidine (100 mg/kg) and the EEOH (100, 250 mg/kg) inhibited gastric ulcer formation by 73%, 55% and 32% respectively. In this exactly model other treatments as cimetidine, FRF and FDF (100 mg/kg) each caused 54%, 36% and 45% inhibition, respectively. In the stress-induced gastric ulcer model, cimetidine (100 mg/kg) and the EEOH (50, 100, 250 mg/kg), inhibited gastric ulcer formation by 63%, 73%, 68% and 69% respectively. In the same model, cimetidine, FRF and FDF (100 mg/kg) significantly protected the gastric mucosal of the mice by 60%, 51% and 47% when compared to the control group. In pylorus-ligated mice, cimetidine (positive control) and FRF significantly decreased gastric acid secretion, increased gastric pH and reduced the acid output when compared to the negative control. FDF had no significant effect on these parameters. The protection provided by FRF probably involved an antisecretory mechanism mediated by flavonoids which were absent in FDF. The amount of adherent mucous in the stomach contents was also evaluated with the treatments carbenoxolone (200 mg/kg), FRF and FDF (100 mg/kg) treatment. Each treatments significantly increased the amount of adherent mucous in the gastric juice (8.67 +/- 1.73, 3.35 +/- 1.59, 2.1 +/- 0.41 mg/g of wet tissue, respectively) compared to the control group, indicating a cytoprotective action on the gastric mucosa. Treatment with FRF plus indomethacin and FDF plus indomethacin reduced the prostaglandin biosyntesis (13.6 +/- 6.5, 27 +/- 5.5 pg/well) by the mucosa, indicating that the cytoprotective action on the gastric mucosa was not related to the level of prostaglandins. Only FDF (38 +/- 17 pg/well) maintained the level of prostaglandins and guaranteed the integrity of the mucosa. The results indicate that the EEOH, FRF and FDF have antisecretory and cytoprotective actions, that may be related to the presence of luteoline in the extract and active fractions.
Keywords: Syngonanthus arthrotrichus; antisecretory; cytoprotective; ulcer; flavonoid